1998
DOI: 10.1111/j.1600-079x.1998.tb00557.x
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin effects on sleep, mood, and cognition in elderly with mild cognitive impairment

Abstract: The effects of immediate-release melatonin on circadian rest-activity profiles, cognition, and mood were investigated in ten elderly individuals with self-reported sleep-wake disturbances. Melatonin (6 mg), administered 2 hr before habitual bedtime, enhanced the rest-activity rhythm and improved sleep quality as observed in a reduction in sleep onset latency and in the number of transitions from sleep to wakefulness. However, total sleep time was not significantly increased nor was wake within sleep significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
74
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(75 citation statements)
references
References 30 publications
(9 reference statements)
1
74
0
Order By: Relevance
“…From our study it has become apparent that the nocturnally restricted melatonin, via the MT1 receptors that are expressed widely throughout the hypothalamus, may not only influence the SCN rhythmicity, but also reinforce the endogenous circadian rhythmicity on other hypothalamic systems. Indeed, besides its circadian function, melatonin has been implicated in the regulation of sleep, reproduction, stress, mood, body temperature, and cognition (Cassone, 1990;Jean-Louis et al, 1998;Pang et al, 1998;Wetterberg, 1999;Krauchi and Wirz-Justice, 2001;Satoh and Mishima, 2001), many of whose functions are mediated by the hypothalamus.…”
Section: Mt-ir Distribution In the Human Hypothalamusmentioning
confidence: 99%
See 1 more Smart Citation
“…From our study it has become apparent that the nocturnally restricted melatonin, via the MT1 receptors that are expressed widely throughout the hypothalamus, may not only influence the SCN rhythmicity, but also reinforce the endogenous circadian rhythmicity on other hypothalamic systems. Indeed, besides its circadian function, melatonin has been implicated in the regulation of sleep, reproduction, stress, mood, body temperature, and cognition (Cassone, 1990;Jean-Louis et al, 1998;Pang et al, 1998;Wetterberg, 1999;Krauchi and Wirz-Justice, 2001;Satoh and Mishima, 2001), many of whose functions are mediated by the hypothalamus.…”
Section: Mt-ir Distribution In the Human Hypothalamusmentioning
confidence: 99%
“…Melatonin acts as a hormonal message of the photoperiod to regulate circadian and seasonal rhythms (Cassone, 1990;Arendt and Skene, 2005). Moreover, melatonin is involved in numerous physiological responses, including sleep regulation, reproduction, stress, mood, body temperature, and cognition (Cassone, 1990;Jean-Louis et al, 1998;Pang et al, 1998;Wetterberg, 1999;Satoh and Mishima, 2001;Krauchi and Wirz-Justice, 2001). Many of these physiological processes are mediated by the hypothalamus and pituitary gland.…”
mentioning
confidence: 99%
“…One of the first studies involving the use of melatonin in MCI patients was conducted in 1998 [31]. The results displayed improvements in rest-activity rhythm, sleep quality, the ability to remember previously learned items, and reductions in reported depression in these patients.…”
Section: Mild Cognitive Impairmentmentioning
confidence: 96%
“…Thus, melatonin supplementation may retard neurodegenerative changes associated with brain aging 131 . A case study revealed that melatonin-treated (6 mg/day) identical twins had less memory loss over 36 months 132 .…”
Section: Melatonin and Neurological Conditionsmentioning
confidence: 99%